International recommendation for a comprehensive neuropathologic workup of epilepsy surgery brain tissue: A consensus Task Force report from the ILAE Commission on Diagnostic Methods - Blümcke, Ingmar; Aronica, Eleonora; Miyata, Hajime; Sarnat, Harvey B; Thom, Maria; Roessler, Karl; Rydenhag, Bertil; Jehi, Lara; Krsek, Pavel; Wiebe, Samuel; Spreafico, Roberto (Epilepsia, 2016)
Epilepsy surgery is an effective treatment in many patients with drug-resistant focal epilepsies. An early decision for surgical therapy is facilitated by a magnetic resonance imaging (MRI)-visible brain lesion congruent with the electrophysiologically abnormal brain region. Recent advances in the pathologic diagnosis and classification of epileptogenic brain lesions are helpful for clinical correlation, outcome stratification, and patient management. However, application of international consensus classification systems to common epileptic pathologies (e.g., focal cortical dysplasia [FCD] and hippocampal sclerosis [HS]) necessitates standardized protocols for neuropathologic workup of epilepsy surgery specimens. To this end, the Task Force of Neuropathology from the International League Against Epilepsy (ILAE) Commission on Diagnostic Methods developed a consensus standard operational procedure for tissue inspection, distribution, and processing. The aims are to provide a systematic framework for histopathologic workup, meeting minimal standards and maximizing current and future opportunities for morphofunctional correlations and molecular studies for both clinical care and research. Whenever feasible, anatomically intact surgical specimens are desirable to enable systematic analysis in selective hippocampectomies, temporal lobe resections, and lesional or nonlesional neocortical samples. Correct orientation of sample and the sample's relation to neurophysiologically aberrant sites requires good communication between pathology and neurosurgical teams. Systematic tissue sampling of 5-mm slabs along a defined anatomic axis and application of a limited immunohistochemical panel will ensure a reliable differential diagnosis of main pathologies encountered in epilepsy surgery.
Keywords: Psychosurgery; Encephalitis; hemisferektomie; Tumor; Hemispherectomy; Malformations of Cortical Development; Internationality; Temporal Lobe; Brain; stereotaktické techniky; Advisory Committees; spánkový lalok; poradní výbory; internacionalita; Practice Guidelines as Topic; Malformation; Glia; Neuropathology; epilepsie; Stereotaxic Techniques; Hippocampus; Research Report; lidé; psychochirurgie; Humans; Seizure; konsensus; Neuron; mozek; Consensus; Epilepsy; malformace mozkové kůry; hipokampus; směrnice pro lékařskou praxi jako téma; výzkumná zpráva